Fabrication of Edible Film from Papaya Extract (Carica Papaya L.) with a Mixture of Tapioca Flour, Wheat Flour, and Glycerine (Journal of Chemical Natural Resources, 2021)
Fabrication of edible film from papaya extract ( Carica papaya L.) with tapioca , wheat and glycerin mixture has been successfully conducted. The edible film was made by mixing papaya extract, tapioca, wheat, and glycerin until homogeneous and poured on the plastic plate then dried in an oven for 2 days at 40ÂºC with the comparison of tapioca: wheat (7.5 g: 2.5 g) and (5 g: 5 g). Edible films produced were then tested for their characteristics and nutrient levels. The results show that the edible film with the comparison of tapioca: wheat (7.5 g: 2.5 g) show a good result with the characteristics which include thickness tensile strength, elastic and SEM that is 0.193 mm; 0, 1442 Kgf/mm-2; 48.82% and making a film with the structure that has tight pores, compatible, and smooth. The levels of nutrients were water, ash, protein, fat, carbohydrates, and beta carotene from the edible film were 16.23 %; 2,921 %; 5.44 %; 1.76 %; 73.65 %, and 116.052 ppm, respectively. The organoleptic test results show good results that the panelist liked the edible film.